Relationship between moderate-to-vigorous physical activity, abdominal fat and immunometabolic markers in postmenopausal women - Diniz, T. A. [UNESP]; Fortaleza, A. C. S. [UNESP]; Buonani, C. [UNESP]; Rossi, F. E. [UNESP]; Neves, L. M. [UNESP]; Lira, F. S. [UNESP]; Freitas-Junior, I. F. [UNESP] (Elsevier B.V., 2015)
Objects: To assess the burden of levels of physical activity, non-esterified fatty acids (NEFA), triacylglycerol and abdominal fat on the immunometabolic profile of postmenopausal women. Study design: Forty-nine postmenopausal women [mean age 59.43 (standard deviation 5.61) years] who did not undertake regular physical exercise participated in this study. Body composition was assessed using dual-energy X-ray absorptiometry, and levels of NEFA, tumour necrosis factor-alpha, adiponectin, insulin and triacylglycerol were assessed using fasting blood samples. The level of physical activity was assessed using an accelerometer (Actigraph GTX3x), and reported as counts/min, time spent undertaking sedentary activities and time spent undertaking moderate-to-vigorous physical activity (MVPA). The following conditions were considered to be risk factors: (i) sedentary lifestyle (<150 min of MVPA per week); (ii) high level (above median) of abdominal fat; and (iii) hypertriacylglycerolaemia (<150 mg/dl of triacylglycerol). Results: In comparison with active women, sedentary women had higher levels of body fat (%) (p = 0.041) and NEFA (p = 0.064). Women with higher levels of abdominal fat had impaired insulin resistance (HOMA-IR) (p = 0.016) and spent more time undertaking sedentary activities (p = 0.043). Moreover, the women with two risk factors or more had high levels of NEFA and HOMA-IR (p < 0.05), as well as an eight-fold higher risk of a high level of NEFA, independent of age (p < 0.05). No significant relationship was found between levels of physical activity, abdominal fat, tumour necrosis factor-a and adiponectin (p > 0.05). Conclusion: Postmenopausal women with a combination of hypertriacylglycerolaemia, a high level of abdominal fat and a sedentary lifestyle are more likely to have metabolic disturbances. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Postmenopausal women; Free fatty acids; Physical activity; Risk factors; Triacylglycerol